Funny math: games during lectures - Suboč, Olga (Lietuvos matematikos rinkinys, 2016)
In this article are introduced some techniques to present mathematical tasks in puzzle or game form to add variety during lectures and help students to uptake new theoretical knowledge and concepts. Sudoku-type puzzles are constructed using basic problems that students solve during practice lectures. Crosswords of concepts are used to summarize through lectures received theoretical knowledge.
Keywords: teaching of mathematics; games; crosswords; sudoku; motivation